PENGARUH ONLINE CUSTOMER REVIEW, ONLINE CUSTOMER RATING, DAN KEPERCAYAAN KONSUMEN, TERHADAP KEPUTUSAN PEMBELIAN PADA MARKETPLACE SHOPEE INDONESIA - Puspita Sari; Fransiscus Amonio Halawa (Journal of Economic, Bussines and Accounting (COSTING), 2026)
This study aims to analyze the influence of Online Customer Reviews, Online Customer Ratings, and Consumer Trust on Purchase Decisions on the Shopee marketplace, both partially and simultaneously. Shopee's dominance as the most frequently accessed e-commerce platform in Indonesia does not guarantee that every visit will result in a purchase decision. Therefore, it is necessary to identify the factors that influence consumers' purchase decisions. This study employed a quantitative method with an associative approach. Data were collected through questionnaires distributed to 116 respondents and analyzed using multiple linear regression with the assistance of IBM SPSS version 27. The results indicate that Online Customer Reviews (t = 4.277), Online Customer Ratings (t = 4.521), and Consumer Trust (t = 3.335) have a positive and significant effect on Purchase Decisions with a significance value of less than 0.05. Simultaneously, these three independent variables also have a positive and significant effect on Purchase Decisions, with an F-value of 84.776, which is greater than the F-table value of 2.69, and a significance value of less than 0.05. Therefore, Online Customer Reviews, Online Customer Ratings, and Consumer Trust are proven to have a positive and significant effect on Purchase Decisions, both partially and simultaneously, on the Shopee marketplace in Indonesia.